The Intangible Concept Behind a Tangible Economic Miracle A calling: what drives China's entrepreneurial class to new heights? - Valdivieso, José Félix (IE Fundation, 2021)
For reasons not worth exploring here, religion is no longer in fashion in the world today, with the exception of the Muslim nations: a certain secularization has spread across the planet. At the very least, religion is no longer fashionable in the traditional sense of the word, as a system of beliefs and practices that bring together the majority of the population of a country or region around a social structure. This traditional concept of religion was introduced in China in the 19th century, through Japan, which has so often served to transmit ideas and trends to its neighbor. Japan coined the word Shūkyō (宗教), religion, and the Chinese borrowed the concept, adopting the same characters, but pronouncing it zōngjiào (宗教). From the first Chinese Republic, after the fall of the Qīng Empire in 1911, to the present day, Buddhism, Taoism, Christianity and Islam have been recognized as religions in this traditional sense. All other religious beliefs and practices, local cults and other types of spiritual manifestations not part of these major religions were relegated to the category of superstitions and beliefs (míxìn 迷信)
Keywords: China; entrepreneurial